2021
DOI: 10.3389/fspor.2021.673452
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Ways to Combat Doping in a Sports Education Context!? A Systematic Review on Doping Prevention Measures Focusing on Young Age Groups

Abstract: Youth is characterized by testing and crossing natural boundaries, sometimes with the help of performance-enhancing substances. In this context, doping prevention measures play a crucial role to protect individuals both within and outside the context of elite sport. Based on the PRISMA guidelines, a systematic literature search was conducted in the databases ProQuest (ERIC), Scopus, PSYNDEX/PsychInfo, PubMed, and Web of Science Core Collection to provide an overview of the impact of doping prevention measures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 84 publications
0
37
0
Order By: Relevance
“…In sum, the extent of education received (no education, information only, comprehensive education) had an impact on almost all markers assessed; as expected, athletes who received comprehensive education scored highest for all markers. In line, a recent systematic review on doping prevention measures targeting young age groups also concluded that programs that actively engage participants are considered to be better than lecture-based knowledge transfer (Pöppel, 2021 ). Regarding the DAL components, educational incongruence seemed to have a negative effect, especially for Critical Literacy.…”
Section: Results Of Phase One—tool Development and Testingmentioning
confidence: 98%
“…In sum, the extent of education received (no education, information only, comprehensive education) had an impact on almost all markers assessed; as expected, athletes who received comprehensive education scored highest for all markers. In line, a recent systematic review on doping prevention measures targeting young age groups also concluded that programs that actively engage participants are considered to be better than lecture-based knowledge transfer (Pöppel, 2021 ). Regarding the DAL components, educational incongruence seemed to have a negative effect, especially for Critical Literacy.…”
Section: Results Of Phase One—tool Development and Testingmentioning
confidence: 98%
“…Models of doping behavior guide the understanding of athletes' behavior and influence how prevention is implemented (Hauw and McNamee, 2015 ). Numerous publications on doping and prevention refer to the theory of planned behavior (Ajzen, 1991 ; Pöppel, 2021 ). They emphasize the impact of positive doping attitudes and perceived social norms as correlates of doping intentions and behavior or extend the theoretical model by adding the use of supplements or self-efficacy to resist doping (Ntoumanis et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the focus on this theory is critically discussed (Petróczi et al, 2017 ). Nevertheless, many doping prevention studies use these variables to evaluate the effectiveness of interventions (Pöppel, 2021 ). Mainly newer approaches highlight the importance of ethics, moral disengagement, or resistance against doping temptations as target variables and broaden the prevention perspective (Elbe and Brand, 2016 ; Hurst et al, 2020 ; Kavussanu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations